2018
DOI: 10.1111/neup.12516
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of V180I genetic Creutzfeldt‐Jakob disease presenting with early disease pathology

Abstract: The patient was a Japanese woman who experienced a decrease in activity and gait disturbance as the initial symptoms at the age of 86, followed by disorientation and memory dysfunction. Magnetic resonance imaging showed extensive cortical regions with hyperintensity in diffusion-weighted images, and these regions showed swelling in T2-weighted and fluid-attenuated inversion recovery (FLAIR) images. The medial occipital cortex and striatum showed no apparent hyperintensity on diffusion-weighted imaging (DWI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 21 publications
4
29
0
Order By: Relevance
“…According to previous autopsy case reports of V180I gCJD, the neurons of the cerebral neocortex in such cases show a tendency toward preservation despite the extensive severe spongiform changes and long disease duration [1,6,7,9,10]. Furthermore, the precentral gyrus and in particular the medial portion of the occipital lobe tend to be pathologically preserved in patients with V180I gCJD [1,9,10]. We believe that these pathological observations appear to support our hypothesis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…According to previous autopsy case reports of V180I gCJD, the neurons of the cerebral neocortex in such cases show a tendency toward preservation despite the extensive severe spongiform changes and long disease duration [1,6,7,9,10]. Furthermore, the precentral gyrus and in particular the medial portion of the occipital lobe tend to be pathologically preserved in patients with V180I gCJD [1,9,10]. We believe that these pathological observations appear to support our hypothesis.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the finding of facial mimicry in the present case, we speculate that the function of both visual recognition, including from the optic nerve to the primary visual cortex in the occipital cortex, and facial movement, including the facial nerve nucleus and primary motor cortex in the precentral gyrus, were preserved, at least during the period that the symptom was observed. According to previous autopsy case reports of V180I gCJD, the neurons of the cerebral neocortex in such cases show a tendency toward preservation despite the extensive severe spongiform changes and long disease duration [1,6,7,9,10]. Furthermore, the precentral gyrus and in particular the medial portion of the occipital lobe tend to be pathologically preserved in patients with V180I gCJD [1,9,10].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous report indicated that the survival period of tube-fed patients with sCJD is longer than that of patients who were not tube fed [20]. To understand the timing of starting tube-fed or total parenteral nutrition (TPN), we reviewed 14 patients with autopsy-confirmed V180I gCJD including the current patient (Table 1) [8,[21][22][23][24][25][26][27][28][29][30][31][32][33]. Combined V180I and M232R gCJD patients were excluded from our review.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several neuropathological features that are associated with the V180I‐129M/PrP Sc type 2 combination, including the florid spongiform change lacking confluent vacuoles, as well as the faint synaptic type pattern of PrP immunostaining, do not fully match those of the sCJDMM2 subtypes .…”
Section: Phenotypic Spectrum and Classification Of Disease Subtypesmentioning
confidence: 98%